The Impact of Hotel Customer Engagement and Service Evaluation on Customer Behavior Intention: The Mediating Effect of Brand Trust - Chen, Xi; Wang, Yifan; Lyu, Xujie; Zhang, Jinlong (Frontiers in Psychology, 2022)
Because of the COVID-19, the tourism industry has been greatly affected, especially the occupancy rate of hotel companies. This study analyzes the effects of customer engagement and service evaluation on brand trust and customer behavioral intention based on 437 valid questionnaires from Chinese economy hotel companies using SPSS and AMOS. The components of customer engagement are subdivided into five dimensions: identification, enthusiasm, attention, absorption and interaction, and the impact of these five dimensions on brand trust in the COVID- 19 is investigated. Finally, it verifies the influence of trust on customers' word-of-mouth (WOM) intention and customers' reuse intention. The results of this study not only enrich the research on customer engagement and service evaluation in marketing circles but also give some advice to hotel companies in the COVID-19 customer engagement and service evaluation that can enhance the trust of enterprises and promote the behavior intention of customers, which has certain practical reference value.